Strategic Decision Making for Family Business's Survivability; Case of CV Karya Agung - Nuswantoro, Bangun; Hermawan, Pri (Journal of Business and Management, 2015)
Abstract- Most businesses have a common goal, which is to maximize shareholder wealth. The profit earned by the company will surely increase the shareholder wealth. As a service business which rely on government projects, the orders from the government will continue to decrease with the uncertainty about the number and value of projects to be implemented by the government and the emergence of new competitors. For that reasons, business strategy is necessary for the family business like the object of this study, CV Karya Agung to survive in the competition. This research is intended to provide recommendations in the best business strategy for the business’s survivability and development of the business.This study began in October 2014 until June 2015. Data collection is done by interview periodically with some key staff in the CV. Karya Agung. From the interview, the obtained data is used to perform business strategy formulation and the data about estimation amount of investment and the estimated profit from each alternatives is used to choose which alternatives is the best using decision tree tools. In the end the output of decision tree is tested by sensitivity analysis how sensitive is the chosen alternative.The results from this research is alternative about expanding business area to Malang city by renting the office. Compared with other alternatives in the given limit time of 1-year period, the other formulated alternatives could not provide more profit than expansion to Malang with renting the office alternatives.In conclusion, researcher provided recommendations for CV Karya Agung to do the expand business operations in Malang area by renting the office in order to obtain more business opportunities and more profits so that their business can survive in the competition. Keywords: Family Business, Decision Making, Business Strategy, Consultant of Construction, Survivability